A clinical primer on intellectual disability - Patel, Dilip R. (Transl Pediatr, 2020)
Between 1% and 3% of persons in general population are estimated to have some degree of intellectual disability. A diagnosis of intellectual disability is based on clinical history, level of intellectual ability and level of adaptive function. Both, the intellectual and adaptive functioning are measured using individually administered standardized tests. More than 75% of persons who have intellectual disability have mild intellectual disability and an underlying specific etiology is less likely to be identified; whereas, in a small percentage of persons with severe intellectual disability, an underlying specific biologic cause is highly likely to be identified. Genetic abnormalities, inborn errors of metabolism and brain malformations are major categories of causes identified in severe to profound intellectual disability. The initial clinical presentation and recognition depends on the severity and underlying cause of intellectual disability. The etiology, severity, cognitive abilities, and adaptive function, vary among persons with intellectual disability and need consideration in developing a treatment plan. The physician plays an essential role in the evaluation, treatment of associated medical conditions and preventive care, and in facilitating and coordinating consultative services and community based care.